Studi Fenomenologi Keterbukaan Diri Remaja Akhir Perempuan Pengguna Aplikasi Kencan Online Bumble di Kota Bandung - Puteri Natasya Brata; Anggian Lasmarito Pasaribu; Alila Pramiyanti (Jurnal Komunikasi Nusantara, 2023)
The emergence of online dating apps which is one of the results of this technological development provides convenience and also changes in people's behavior. Online dating applications provide an opportunity for individuals to leave traditional ways of socializing and facilitate individuals by providing a wide choice of types of partners. One of the most popular online dating apps in Indonesia is Bumble. The presence of the Bumble application creates a new era in the world of online dating because conversations can only be initiated by the female side. In searching for an ideal partner on Bumble, it is necessary to develop interpersonal relationships. The formation of these relationships requires self-disclosure. This research was conducted to find out how self-disclosure of late adolescent girls who use the online dating application Bumble in the city of Bandung. Researchers used qualitative methods and a phenomenological approach with the aim of interpreting self-disclosure based on the experiences of informants. This study refers to the theory of self-disclosure based on the types of messages, dimensions, and stages of self-disclosure. The results of this study indicate that there are differences in the level of self-disclosure in each informant. The difference in self-disclosure is influenced by the involvement of the five dimensions that are quantity, value, accuracy/honesty, purpose, and intimacy. In addition, factors that affect the level of self-disclosure are the character of the informant, the motivation for using the Bumble application, cultural background, the person you are talking to, and the topic of conversation. Abstrak Kemunculan aplikasi kencan online yang merupakan salah satu hasil dari perkembangan teknologi ini memberikan kemudahan dan juga perubahan dalam perilaku masyarakat. Aplikasi kencan online memberikan kesempatan individu untuk meninggalkan cara tradisional bersosialisasi serta memfasilitasi individu dengan menyediakan beragam pilihan tipe pasangan. Salah satu aplikasi kencan online yang populer di Indonesia adalah Bumble. Kehadiran aplikasi Bumble menciptakan era baru dalam dunia kencan online karena percakapan hanya dapat dimulai oleh pihak perempuan. Dalam melakukan pencarian pasangan ideal di aplikasi Bumble diperlukan pembangunan hubungan interpersonal. Pembentukan hubungan tersebut memerlukan adanya keterbukaan diri. Penelitian ini dilakukan untuk mengetahui bagaimana keterbukaan diri remaja akhir perempuan pengguna aplikasi kencan online Bumble di Kota Bandung. Peneliti menggunakan metode kualitatif dan pendekatan fenomenologi dengan tujuan menginterpretasikan keterbukaan diri berdasarkan pengalaman informan. Penelitian ini mengacu pada teori keterbukaan diri berdasarkan jenis pesan, dimensi, serta tahapan keterbukaan diri. Hasil penelitian ini menunjukkan bahwa terdapat perbedaan tingkatan keterbukaan diri pada setiap informan. Perbedaan keterbukaan diri tersebut dipengaruhi oleh keterlibatan lima dimensi yaitu kuantitas, nilai, akurasi/kejujuran, tujuan, dan keakraban. Selain itu, faktor yang mempengaruhi tingkatan keterbukaan diri adalah karakter informan, motivasi penggunaan aplikasi Bumble, latar belakang budaya, lawan bicara, dan topik percakapan.